2018
DOI: 10.1080/17458080.2018.1475759
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-based synthesis of strontium hexaferrite cobalt iron oxide nanoparticles and their biocompatibility in albino mice

Abstract: A number of strontium-based iron oxides are available for the industrial use. Among them, strontium hexaferrite cobalt iron oxide (Sr 2 Co 2 Fe 12 O 22) is preferred over others due to its better magnetic and electrical properties than others. This material is also extensively used for the absorption of microwave radiations. This study was conducted to account for the synthesis and characterization of Sr 2 Co 2 Fe 12 O 22 nanoparticles and to report their biocompatibility in albino mice. Nanoparticles were syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the current study, MDA levels were elevated in the liver and kidney tissue homogenates after NiO-NPs exposure, confirming its oxidative stress activity. MDA is a tissue damage and lipid peroxidation (LPO) marker ( Aitken and Roman, 2008 ), and due to the increased membranes’ permeability after cell damage, enzymatic activity was seen in the extracellular fluid and serum; a considerable rise in MDA concentration in the liver and kidney tissues implies an increase in phospholipase activity and excess release of lipid peroxyl radicals ( Ali, 2019 ), ( Akhtar et al, 2018 ). NiO-NPs have previously been proven to produce free radicals and induce oxidative stress ( Dumala et al, 2018 ), ( Tsao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, MDA levels were elevated in the liver and kidney tissue homogenates after NiO-NPs exposure, confirming its oxidative stress activity. MDA is a tissue damage and lipid peroxidation (LPO) marker ( Aitken and Roman, 2008 ), and due to the increased membranes’ permeability after cell damage, enzymatic activity was seen in the extracellular fluid and serum; a considerable rise in MDA concentration in the liver and kidney tissues implies an increase in phospholipase activity and excess release of lipid peroxyl radicals ( Ali, 2019 ), ( Akhtar et al, 2018 ). NiO-NPs have previously been proven to produce free radicals and induce oxidative stress ( Dumala et al, 2018 ), ( Tsao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials are known to induce oxidative stress in living systems by generating reactive oxygen species (ROS), affecting normal gene expression, resulting in a number of disease conditions [ 23 ]. In order to counter this ROS-mediated toxicity, cells have an antioxidant system consisting of enzymes and non-enzyme biomarkers of oxidative stress that try to maintain normal cellular functioning [ 8 , 24 ]. In the present study, a significant increase in brain SOD levels was observed in high-dose nanocomposite-treated male albino mice ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neodymium is commonly used in the manufacture of audio systems, magnets, hybrid engines, hard drives of laptops and wind turbines; all of these materials are part of our daily lives [ 6 ], while Zinc Sulfide is commonly used in optical sensors, photoconductors and in dielectric filters [ 7 ]. Despite these nanomaterials having a variety of uses and advantages, their safe limits and toxicity have never been explored and it is the need of the hour to determine the biocompatibility of these nanomaterials before their large-scale commercial use to counter their adverse effects to organisms and their environment [ 8 , 9 ]. Recently, we reported that the oral supplementation of Neodymium Zirconate Zinc Sulfide results in disturbed exploratory behavior and muscle activity of albino mice [ 7 ].…”
Section: Introductionmentioning
confidence: 99%